PCR based detection of helicobacter pylori compared with CLO in stomach biopsy samples from patients with dyspepsia: a pilot study - Zaker, Bushra Binte; Akhond, Saraf; Nahar Nanchi, Shomia (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2023.